URGENSI PEMBERLAKUAN LEX SPORTIVA APABILA TERDAPAT UNSUR PIDANA PADA KASUS PENGATURAN SKOR OLAHRAGA SEPAKBOLA - Iqbal Hirzi Romadhon; Slamet Suhartono (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Along with the rapid growth of social, educational, cultural, and other aspects of people's life, there has also been an increase in many forms of crimes or infractions, one of which is score fixing in sports. As the world's parent organization of football, FIFA has its own constitution, rules, and legal system. It's called the Lex Sportiva. The normative legal research approach was utilized in this article. Whereas the normative legal approach is a technique that is carried out via research on library resources that are secondary data to solve and resolve the concerns of legal difficulties encountered. Fixing the score in a sports event is viewed as an issue that harms the public interest since it jeopardizes the integrity of a competition, jeopardizes societal values and cultural education expressed in sports, and jeopardizes a sport's income. Criminal law is a coercive legislation that states that any criminal activities that meet the criteria of a crime shall be prosecuted criminally. The collaboration of PSSI and the National Police in score setting is also regarded as vital in creating a healthy and clean Indonesian football environment. So that the PSSI statute has a clear position in the eyes of national law, both the distribution of authority and the application of punishment must be made down in laws and regulations that are consistent with the types of laws and regulations that exist in Indonesia